A comparative study of organic gutta - percha solvents on different gutta - percha brand - Asuncion, Ramil L.
Root canal fillings are removed by gutta- percha solvents. These solvents can either be essential oils such as eucalyptol or organic solvents like chloroform. The latter are compared for their effect on three brands of gutta- percha- Roeke, Diadent and Superendo. Chloroform was the most effective solvent followed by xylene. superendo was the most soluble gutta-percha brand regardless of solvent used.